Clinical outcomes for patients on antiplatelet and anticoagulants in thoracoabdominal trauma - Victoria Sharp, DO, FACS, FACOS; Rola Bazzi, PharmD; Jason P. Hecht, PharmD, BCPS, BCCCP, FCCM (Surgery Open Science, 2023)
Introduction: Trauma outcomes can be greatly affected by antiplatelet and anticoagulant (AP/AC) use. The goal of this study was to compare outcomes in trauma patients on AP/AC undergoing emergent surgery for thoracoabdominal trauma at 35 level 1 and 2 trauma centers from 2014 to 2021. Methods: This was a retrospective cohort study of 2460 adult patients with a chest, abdomen, or pelvis abbreviated injury score (AIS) of 2 or more who underwent surgery within 24 h of admission. These patients were segregated into four main cohorts based on antiplatelet/anticoagulation use: those not on AP/AC, those taking direct-acting oral anticoagulants (DOACs), those taking clopidogrel, and those taking warfarin. Patients were excluded if they had surgery >24 h after presentation, were dead on arrival, or had any other body system AIS score of 3 or higher. Results: The mean injury severity score (ISS) in all four groups ranged from 16.3 to 18.6 (p = 0.834) with a mean time to operating room from 208 to 478 min (p < 0.001). Laparotomy was performed in 60 to 71 % (p > 0.01) of patients, regardless of AP/AC status, and thoracic procedures were performed in 3.1 to 9.3 % (p = 0.42) of patients. In-hospital mortality and hospice rates were highest in the clopidogrel group at 21.9 %, followed by warfarin at 13 %, DOACs at 15 %, and no AP/AC at 7.63 % (p = 0.008). Serious complications occurred in 61 % of patients on warfarin, 50 % of those on DOACs, and 44 % of those on clopidogrel. All of these groups demonstrated significantly higher complication rates than patients in the no AP/AC control group at 25 % (p < 0.001). Total transfusion of packed red blood cells and fresh frozen plasma did not differ significantly between the groups; however, 24-h platelet transfusion did. Patients on clopidogrel received 14 packs of platelets, while those on warfarin and DOACs received 8 and 13 packs respectively (p = 0.011). Patients on warfarin had the longest hospital length of stay (LOS) at 13 days and ICU LOS at 9 days, compared to those on DOACs (8 and 4), those on clopidogrel (7 and 3), and those not taking AC/AP (7 and 4) (hospital LOS p = 0.03, ICU LOS p = 0.019). Those on AC/AP were also noted to be significantly older than those on neither, with those taking these medications averaging out to be approximately 69 years old and those not on these medications averaging 37 years old (p < 0.001). Conclusion: There was significantly higher mortality in patients on clopidogrel and increased length of stay and risk of serious complications in patients taking DOACs and warfarin. In patients on AP/AC there was also a significantly longer time to surgery than in those not taking either. Given these associations trauma surgeons should consider intervening sooner on patients taking AP/AC on admission, as the delay to intervention may contribute to the risks for trauma patients and result in worse outcomes as well as higher rates of mortality.